A common origin of the 4143insA ADAMTS13 mutation - Schneppenheim, Reinhard; Hovinga, Johanna A. Kremer; Becker, Tim; Budde, Ulrich; Karpman, Diana; Brockhaus, Wolfgang; Hrachovinová, Ingrid; Korczowski, Bartosz; Oyen, Florian; Rittich, Šimon; von Rosen, Johannes; Tjønnfjord, Geir E.; Pimanda, John E.; Wienker, Thomas F.; Lämmle, Bernhard (Thrombosis and Haemostasis, 2006)
Severely deficient activity of the von Willebrand Factor (VWF) cleaving metalloprotease,ADAMTS13, is associated with thrombotic thrombocytopenic purpura (TTP).The mutation spectrum of ADAMTS13 is rather heterogeneous,and numerous mutations spread across the gene have been described in association with congenital TTP. The 4143insA mutation is unusual with respect to its geographic concentration. Following the initial report from Germany in which the 4143insA mutation was detected in four apparently unrelated families, we have now identified this mutation in a further eleven patients from Norway, Sweden, Poland, Germany, the Czech Republic and Australia. Confirmation that the Australian patient is of German ancestry, together with the Northern and Central European origin of most of the other patients, suggests that the 4143insA mutation has a common genetic background. We established ADAMTS13 haplotypes by analyzing 17 polymorphic intragenic markers. The haplotypes linked to 4143insA were identical in all informative families. Three novel candidate mutations, C347S, P671L and R1060W, as well as the known mutation R507Q, were also identified during the course of the study. We conclude that 4143insA has a common genetic background and is frequent among patients with hereditary ADAMTS13 deficiency in Northern and Central European countries.
Keywords: ADAMTS13; TTP; VWF; mutation